Programming embedded systems : with C and GNU development tools - Barr, Michael, 1971- (O'Reilly, 2006)
If you have programming experience and a familiarity with C--the dominant language in embedded systems--Programming Embedded Systems, Second Edition is exactly what you need to get started with embedded software. This software is ubiquitous, hidden away inside our watches, DVD players, mobile phones, anti-lock brakes, and even a few toasters. The military uses embedded software to guide missiles, detect enemy aircraft, and pilot UAVs. Communication satellites, deep-space probes, and many medical instruments would have been nearly impossible to create without embedded software.- Resumé vydavatel